2019
DOI: 10.1093/pcp/pcz101
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Yellow Flowers of the Japanese Morning Glory by Engineering Its Flavonoid Biosynthetic Pathway toward Aurones

Abstract: Wild-type plants of the Japanese morning glory (Ipomoea nil) produce blue flowers that accumulate anthocyanin pigments, whereas its mutant cultivars show wide range flower color such as red, magenta and white. However, I. nil lacks yellow color varieties even though yellow flowers were curiously described in words and woodblocks printed in the 19th century. Such yellow flowers have been regarded as ‘phantom morning glories’, and their production has not been achieved despite efforts by breeders of I. nil. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Genetically engineered plants with altered lignin composition and content are being applied in the pulp and paper industry to improve pulp yields and decrease energy consumption and environmental pollution, and in forage grasses to improve digestibility (Chabannes et al, 2001; Chanoca et al, 2019; Halpin, 2019). In addition, MFR through manipulation of flavonoid structural genes gives rise to flowers with novel colors in horticultural plants (Hoshino et al, 2019). With the rapid advancement of metabolic engineering and precise genome editing, the genetic control of metabolic flux of phenylpropanoid metabolism using a molecular design strategy is a promising approach to breeding high‐yield, stress‐resistant, and high‐nutritional content crops.…”
Section: Discussionmentioning
confidence: 99%
“…Genetically engineered plants with altered lignin composition and content are being applied in the pulp and paper industry to improve pulp yields and decrease energy consumption and environmental pollution, and in forage grasses to improve digestibility (Chabannes et al, 2001; Chanoca et al, 2019; Halpin, 2019). In addition, MFR through manipulation of flavonoid structural genes gives rise to flowers with novel colors in horticultural plants (Hoshino et al, 2019). With the rapid advancement of metabolic engineering and precise genome editing, the genetic control of metabolic flux of phenylpropanoid metabolism using a molecular design strategy is a promising approach to breeding high‐yield, stress‐resistant, and high‐nutritional content crops.…”
Section: Discussionmentioning
confidence: 99%
“…As it is a food with high nutritional value, research on yellow mushroom is imminent, but the molecular mechanisms of the yellow phenotype are still unclear. So far, a number of studies have reported that carotenoids, flavonoids, and other compounds contribute to the yellow flower color or fruit color of angiosperms, but few studies focus on fungi [ 11 , 12 ]. In the absence of chloroplasts, the yellow phenotype of yellow mushroom may be quite different [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…AS, a homolog of plant polyphenol oxidase (PPO), catalyzes the 4-monohydroxylation or 3,4-dihydroxylation of ring B to produce aurone, followed by oxidative cyclization by oxygenation [ 49 ]. Both in Ipomoea nil [ 50 ] and Torenia [ 45 ], the co-overexpression of the AmCH4′GT and AmAS1 genes leads to the accumulation of aurone 6- O -glucoside. Furthermore, various classical substitution patterns, such as hydroxylation, methoxylation, and glycosylation, lead to the formation of a series of aurone compounds, with over 100 structures having been reported to date [ 48 ].…”
Section: Flavonoid Biosynthesis In Plantsmentioning
confidence: 99%